ACCOUNTING FOR CARBON NEUTRALITY corporate accountability in the hydrogen economy. - Di Vaio, Assunta (Routledge studies in accounting., 2025)
Despite the progress made so far, the links between environmental, social and governance (ESG) sustainability pillars remain underexplored, particularly in the context of firms investing in hydrogen for decarbonization. In essence, hydrogen is a lynchpin connecting engineering ingenuity, economic viability, and strategic business decisions. Its multifaceted role underscores its significance in addressing contemporary challenges, driving innovation, and shaping a sustainable future through the accounting system. This book unravels the complexities of carbon control practices, offering insights into financial, operational, and sustainable dimensions. From the challenges of sustainability transitions and technology adoption to utilize renewable resources and disclosing decarbonization practices, the book explores the critical role of accounting tools and international regulatory frameworks like the United Nations 2030 Agenda, the European Union Green Deal, and Paris Agreement as organizational collective responsibility in shaping a sustainable future. By incorporating stakeholder, stewardship, legitimacy, institutional, resource dependency theories, the book bridges gaps in academic research and offers a fresh perspective on decarbonization in the hydrogen sector. The qualitative methodology provides a unified vision from strategies to implementation, guiding companies toward the contribution of the carbon neutrality goal in the hydrogen economy while ensuring accountability for their actions, conduct, and sustainability reporting.